Experimental analysis of turbulent boundary layer under the influence of adverse pressure gradient - Materny, M.; Dróżdż, A.; Drobniak, S.; Elsner, W. (Archives of Mechanics, 2008)
The paper deals with the experimental analysis of turbulent boundary layer at the flat plate for large value of Reynolds number equal Reθ≈3000. The adverse pressure gradient is generated by curvature of the upper wall and corresponds to the case of pressure variation in axial compressor. The analysis is concentrated on the problem of scaling of turbulent boundary layer and on the physical background behind scaling laws being compared. The results obtained suggest, that boundary layer at APG conditions requires two velocity scales, i.e. inner (imposed by inner boundary condition) and outer (imposed by outer layer) velocity scales.